A Literature Review of Prone Position in Non-intubated Patients with COVID-19 as a Useful Maneuver to Avoid Mechanical Ventilation - Daniel, Juárez-Villa; Pablo, Mora-Ruiz; Carlos, Sáenz-Luna; Luis, Zavala-Jonguitud; Arturo, Olascoaga-Lugo; Guillermo, Flores; Iván, Zepeda-Quiroz (Highlights on Medicine and Medical Research Vol. 11, 2021)
The spectrum of coronavirus disease 2019 (COVID-19) ranges from asymptomatic to acute respiratory distress syndrome (ARDS). Prone position has been widely used in ARDS patients with mechanical ventilation and its benefits have been proven. The prone position in the awake patient is a different procedure than in the patient under invasive mechanical ventilation. This maneuver can be extrapolated to non-intubated patients with COVID-19, avoiding mechanical ventilation in some patients. Previous reports have demonstrated the benefits of this intervention.